Cost Overrun at the Norwegian Continental Shelf: The Element of Surprise - Atle Oglend; Petter Osmundsen; Sindre Lorentzen (Center for Economic Studies and ifo Institute (CESifo), 2016)
We examine drivers of cost overruns in Norwegian development projects in the oil and gas sector. The multivariate longitudinal econometric analysis employs a unique and detailed dataset consisting of 80 different projects between 2000 and 2015. Among the significant results, we find that the unexpected change in economic activity has a positive effect on the overruns; there is a considerable positive momentum in the transitional cost overruns; more experienced operators tend to incur less overruns; finally, that the size of the investment of the projects has a positive impact on the overruns. Further, we find evidence that the current economic activity matters to an extent, but it is the unexpected change in activity that is the pivotal factor.
Keywords: C51; D22; C31; 330; cost overrun; cost estimation; estimation error